New body scales reveal body dissatisfaction, thin-ideal, and muscularity-ideal in males - Ralph-Nearman, Christina; Filik, Ruth (SAGE, 2018)
The aim of the current study was to develop, test, and re-test two new male body dissatisfaction scales: The Male Body Scale (MBS; consisting of emaciated to obese figures) and the Male Fit Body Scale (MFBS; consisting of emaciated to muscular figures). These scales were compared to the two most commonly used visually-based indices of body dissatisfaction (Stunkard Figure Rating Scale, SFRS; and Somatomorphic Matrix, SM). Male participants rated which body figure on each scale most represented their current figure, then their ideal figure, and then rated which one of the three scales (MBS, MFBS, and SFRS) best represented their current and ideal body overall. Finally, they completed the Drive for Muscularity Scale (DMS), the Eating Disorder Examination Questionnaire (EDE-Q 6.0), and their actual body composition was calculated. This was followed by a re-test and manipulation check two to six weeks later. Participants’ actual body mass index, fat- and muscularity-percentage were all highly related to their current body figure choice, and both new scales were consistently valid and more reliable between test and re-test than the SFRS and SM body dissatisfaction scores. Importantly, each scale was sensitive to different types of body dissatisfaction within males. Specifically, the MBS revealed that males’ desire for the thin-ideal significantly corresponded to higher eating disorder tendencies as identified by EDE-Q 6.0 scores, whilst the MFBS revealed much higher body dissatisfaction toward the larger, muscularity-ideal, predicting higher drive for muscularity as identified by DMS scores. Results validated the new scales, and inform male-focused eating disorder research.